It Takes Two: Endothelial-Perivascular Cell Cross-Talk in Vascular Development and Disease - Sweeney, Mark; Foldes, Gabor (Frontiers in Cardiovascular Medicine, 2018)
The formation of new blood vessels is a crucial step in the development of any new tissue both during embryogenesis and in vitro models as without sufficient perfusion the tissue will be unable to grow beyond the size where nutrition and oxygenation can be managed by diffusion alone. Endothelial cells are the primary building block of blood vessels and are capable of forming tube like structures independently however they are unable to independently form functional vasculature which is capable of conducting blood flow. This requires support from other structures including supporting perivascular cells and the extracellular matrix. The crosstalk between endothelial cells and perivascular cells is vital in regulating vasculogenesis and angiogenesis and the consequences when this is disrupted can be seen in a variety of congenital and acquired disease states. This review details the mechanisms of vasculogenesis in vivo during embryogenesis and compares this to currently employed in vitro techniques. It also highlights clinical consequences of defects in the endothelial cell – pericyte cross-talk and highlights therapies which are being developed to target this pathway. Improving the understanding of the intricacies of endothelial – pericyte signalling will inform pathophysiology of multiple vascular diseases and allow the development of effective in vitro models to guide drug development and assist with approaches in tissue engineering to develop functional vasculature for regenerative medicine applications.